Design of a Multi-Pinhole Collimator for I-123 DaTscan Imaging on Dual-Headed SPECT Systems in Combination with a Fan-Beam Collimator - King, Michael A. (IEEE Trans Nucl Sci, 2016)
For the 2011 FDA approved Parkinson’s Disease (PD) SPECT imaging agent I-123 labeled DaTscan, the volume of interest (VOI) is the interior portion of the brain. However imaging of the occipital lobe is also required with PD for calculation of the striatal binding ratio (SBR), a parameter of significance in early diagnosis, differentiation of PD from other disorders with similar clinical presentations, and monitoring progression. Thus we propose the usage of a combination of a multi-pinhole (MPH) collimator on one head of the SPECT system and a fan-beam on the other. The MPH would be designed to provide high resolution and sensitivity for imaging of the interior portion of the brain. The fan-beam collimator would provide lower resolution but complete sampling of the brain addressing data sufficiency and allowing a volume-of-interest to be defined over the occipital lobe for calculation of SBR’s. Herein we focus on the design of the MPH component of the combined system. Combined reconstruction will be addressed in a subsequent publication. An analysis of 46 clinical DaTscan studies was performed to provide information to define the VOI, and design of a MPH collimator to image this VOI. The system spatial resolution for the MPH was set to 4.7 mm, which is comparable to that of clinical PET systems, and significantly smaller than that of fan-beam collimators employed in SPECT. With this set, we compared system sensitivities for three aperture array designs, and selected the 3 × 3 array due to it being the highest of the three. The combined sensitivity of the apertures for it was similar to that of an ultra-high resolution fan-beam (LEUHRF) collimator, but smaller than that of a high-resolution fan-beam collimator (LEHRF). On the basis of these results we propose the further exploration of this design through simulations, and the development of combined MPH and fan-beam reconstruction.